Human Salivary Histatin-1 Attenuates Osteoarthritis through Promoting M1/M2 Macrophage Transition - Antong Wu; Janak Lal. Pathak; Xingyang Li; Wei Cao; Wenchao Zhong; Mingjing Zhu; Qiuyu Wu; Wanyi Chen; Qiao Han; Siqing Jiang; Yuzhuo Hei; Ziyi Zhang; et al. (MDPI AG, 2023)
Osteoarthritis (OA) is an inflammation-driven degenerative joint disease. Human salivary peptide histatin-1 (Hst1) shows pro-healing and immunomodulatory properties. but its role in OA treatment is not fully understood. In this study, we investigated the efficacy of Hst1 in the inflammation modulation-mediated attenuation of bone and cartilage damage in OA. Hst1 was intra-articularly injected into a rat knee joint in a monosodium iodoacetate (MIA)-induced OA model. Micro-CT, histological, and immunohistochemical analyses showed that Hst1 significantly attenuates cartilage and bone deconstruction as well as macrophage infiltration. In the lipopolysaccharide-induced air pouch model, Hst1 significantly reduced inflammatory cell infiltration and inflammation. Enzyme-linked immunosorbent assay (ELISA), RT-qPCR, Western blot, immunofluorescence staining, flow cytometry (FCM), metabolic energy analysis, and high-throughput gene sequencing showed that Hst1 significantly triggers M1-to-M2 macrophage phenotype switching, during which it significantly downregulated nuclear factor kappa-B (NF-κB) and mitogen-activated protein kinases (MAPK) signaling pathways. Furthermore, cell migration assay, Alcian blue, Safranin O staining, RT-qPCR, Western blot, and FCM showed that Hst1 not only attenuates M1-macrophage-CM-induced apoptosis and matrix metalloproteinase expression in chondrogenic cells, but it also restores their metabolic activity, migration, and chondrogenic differentiation. These findings show the promising potential of Hst1 in treating OA.